2019
DOI: 10.35649/kubr.2018.13.12.1
|View full text |Cite
|
Sign up to set email alerts
|

Use of Social Media in Election Marketing in Bangladesh: Its Impact on Voting Behavior

Abstract: Purpose: The main purpose of the study is to illustrate the use of social media in election marketing in Bangladesh and to identify how social media is changing voting behavior of voters. Social media marketing involves the use of online social media tools—such as Facebook, Twitter, Instagram and LinkedIn—to reach voters in innovative ways. In previous years, traditional media play a significant role in creating awareness among people, but over a period of time social media becomes an important marketing tool … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…This aligns with some research findings that there is a generally positive relationship between social media use and civic and political participation (e.g., Gil de Zúñiga, Jung, & Valenzuela, 2012). Likewise, Balo and Shawon's (2018) study also showed that political leaders and voters through online political campaigns have strong linkage, which builds public confidence in politicians. Moreover, Facebook is a big platform for socialization and offers its users to upload and share text, pictures, and videos (Gould, 2015).…”
Section: Online Political Participationsupporting
confidence: 89%
See 2 more Smart Citations
“…This aligns with some research findings that there is a generally positive relationship between social media use and civic and political participation (e.g., Gil de Zúñiga, Jung, & Valenzuela, 2012). Likewise, Balo and Shawon's (2018) study also showed that political leaders and voters through online political campaigns have strong linkage, which builds public confidence in politicians. Moreover, Facebook is a big platform for socialization and offers its users to upload and share text, pictures, and videos (Gould, 2015).…”
Section: Online Political Participationsupporting
confidence: 89%
“…Elsewhere, Balo and Shawon (2018) emphasized that social media usage corresponds to political awareness among the people of Bangladesh. This study indicates that increased social media usage resulted in political awareness, political rights, and voter power.…”
Section: Online Political Participationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current age of communication, Facebook has transformed the process of political communication. Firstly, it raised people's interest and participation, and secondly, it reduced the direct and indirect communication gap between people and government (Balo & Shawon, 2018). People around the world use social networking applications such as Facebook to get the latest political news and information, which convert young voters into loyal voters (Somaiah, 2018), expanding access to social media increases political participation (Shehzad et al, 2021), active users of social networking sites are active participants of offline political activities, Political parties, candidates and political workers motivate voters to win elections, to enhance the legislative process and influence government policies (Aleyomi & Olanrewaju, 2014).…”
Section: Offline Political Participationmentioning
confidence: 99%